2005
DOI: 10.1111/j.1460-9568.2005.03942.x
|View full text |Cite
|
Sign up to set email alerts
|

19‐Nortestosterone influences neural stem cell proliferation and neurogenesis in the rat brain

Abstract: Abuse of androgenic anabolic steroids can affect brain function leading to behavioural changes. In this study, the effects of the testosterone analogue, 19-nortestosterone, on rat neural stem cells was examined. The androgen receptor is expressed by cultured embryonic and adult neural stem cells, and is also present in the ventricular epithelium during development and in the adult brain in, among others, dentate gyrus. In neural stem cells stimulated with epidermal growth factor, nandrolone reduced cell prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 32 publications
4
100
1
1
Order By: Relevance
“…Nandrolone (19-Nortestosterone) reduces cell proliferation in neural stem cells stimulated with epidermal growth factor, which can be reversed by flutamide, a receptor antagonist. Nandrolone also decreases the BrdU labeling of neural stem cells in the dentate gyrus, indicating reduced cell proliferation in vivo (125). These observations serve to emphasize the differential role of gender specific hormones on neural cell ontogeny.…”
Section: Neural Stem Cellsmentioning
confidence: 66%
“…Nandrolone (19-Nortestosterone) reduces cell proliferation in neural stem cells stimulated with epidermal growth factor, which can be reversed by flutamide, a receptor antagonist. Nandrolone also decreases the BrdU labeling of neural stem cells in the dentate gyrus, indicating reduced cell proliferation in vivo (125). These observations serve to emphasize the differential role of gender specific hormones on neural cell ontogeny.…”
Section: Neural Stem Cellsmentioning
confidence: 66%
“…Previous studies showed that 19-NT and its metabolite residues in meat produce a series of adverse effects, such as peliosis hepatitis, nephromegaly, adrenal atrophy, hypoproteinemia, semen scarcity, testicle shrink, menstrual cycle disorder, cerebral dysfunction, dyssecretosis, emotional instability, and masculinization in children and women (Heitzman, 1976;Bagatell and Bremner, 1996;Bahrke and Yesalis, 2004;Brännvall et al, 2005). Therefore, the use of natural and synthetic hormones for growth promotion purpose in meat-producing animals has been prohibited in the This has resulted in the development of a broad range of methods to detect this drug and its metabolites in biological matrices.…”
Section: Introductionmentioning
confidence: 99%
“…This effect was also observed in primary culture of hippocampal neurons, in which the incubation for 48 hours with 17β-trenbolone significantly decreased cell viability [80]. Furthermore, administration of nandrolone decanoate (15 mg/kg, daily) for 5 days in adult males, females, and pregnant female rat (embryonic day 15) resulted in a significant decrease of BrdU-labeled cells in the dentate gyrus of the hippocampus, indicating that AS overdose decreased cell proliferation [123].…”
Section: Long-term As Abuse and Cognitive Impairmentsmentioning
confidence: 60%
“…Worth of noting long-term administration of nandrolone decanoate (10 mg/kg/week, for 8 weeks) in rats significantly decreased neuronal density not only in the dentate gyrus but also throughout CA1, CA2, CA3, pre-frontal cortex, and parietal cortex [79]. Noteworthy, the dentate gyrus is one of the few regions of the adult brain to exhibit neurogenesis and acute nandrolone administration decreased the number of newly born neurons within dentate gyrus of adult rats in approximately 75%, implying that short-term administration of AS is enough to significantly impair neurogenic processes [123]. Furthermore, neuronal loss and impaired neurogenesis in the hippocampal and cortical structures have been correlated to the development of Alzheimer's disease-related cognitive decline, as well as to increased number of Aβ plaques in this region [127].…”
Section: Long-term As Abuse and Cognitive Impairmentsmentioning
confidence: 99%